N-[4-Acetyl-5-(3-methoxyphenyl)-4,5-dihydro-1,3,4-thiadiazol-2-yl]acetamide - S. Amirthaganesan (Acta Crystallographica Section E, 2008)
The title compound, C13H15N3O3S, crystallizes with two molecules in the asymmetric unit. The thiadiazole rings in both the molecules adopt an envelope conformation. The crystal packing is stabilized by intermolecular N—H...O and C—H...O interactions.